Alternative theories of gravity and neutron stars - Soldateschi, Jacopo; Bucciantini, Niccolò (Il Colle di Galileo, 2021)
General relativity is the currently accepted theory describing how gravity works. In spite of its incredible success, over the years some problems have emerged, both in explaining some astronomical phenomena and in grasping the theory from the purely conceptual point of view. In this work, we show how a particular class of theories which extend general relativity modify the structure and the features of the most extreme stars, neutron stars.